7β‐hydroxycholesterol increases amyloidogenic pathway and may serve as a peripheral biomarker of Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Ha, Junghee; Cho, So Yeon; Lee, Jimin; Kim, Hyunjeong; Choi, Man Ho; Kim, Eosu
Abstract: Background: Oxidized cholesterols have been related to Alzheimer's disease (AD). However, the role of 7β‐hydroxycholesterol (7β‐OHC) in AD pathogenesis is largely unexplored: There is a lack of understanding of whether the increase in 7β‐OHC levels in AD is a consequence of neurodegeneration process or 7β‐OHC plays a direct role in AD pathogenesis. Thus, we aimed to explore the potential of 7β‐OHC as a biomarker of AD and to observe the direct effect of 7β‐OHC on AD pathologies. Method: 7β‐OHC levels in scalp hairs were assessed by gas chromatography‐mass spectrometry (GC‐MS) methods in persons with normal cognition (NC, n = 82), mild cognitive impairment (MCI, n = 39) and AD (n = 81). Also, we examined the relationship between hair 7β‐OHC levels and various clinical features representing cognitive status. Upon stereotaxic injection of 7β‐OHC into the hippocampus of mice, we investigated AD pathologies such as β‐amyloid, tau, and neuroinflammation. We also assessed the behavioral effects of intracerebroventricular injection of 7β‐OHC using the touchscreen‐based 5‐choice serial reaction time task (5‐CSRTT). Result: 7β‐OHC levels were increased in hairs of persons with AD compared to those with NC ( p = 0.001). There was also a significant correlation between hair 7β‐OHC levels and the scores of Mini‐Mental State Examination (MMSE) and Global Deterioration Scale (GDS) after controlling age, gender, education, and statin use. In the animal experiment, we found that hippocampal 7β‐OHC injection induces microglial and astrocytic activation and increases levels of interleukin (IL)‐1β and IL‐6, suggesting neuroinflammation. It also promoted the amyloidogenic pathway by upregulating BACE 1 while downregulating alpha‐secretase, TACE. In the behavioral assessment, we found that 7β‐OHC treatment increases perseveration, compatible with frontal lobe dysfunction. Conclusion: Our results suggest that 7β‐OHC in scalp hair could serve as a convenient peripheral biomarker of AD. Given that accumulative levels of steroid molecules in hairs indicate its plasma exposure levels in the past several months, our study also suggests that increased plasma 7β‐OHC may be a preceding factor that can increase AD pathology.